Design & development of electric cable inspection - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Mostafa, Mohammad Golam; Hossain, Belayet; Salam, S. M.; Nithe, N. A.; Aziz, M. A.; Halder , S (Global Journals Inc. (USA), 2016)
Previously, electric cable inspection are being done by human. With the advancement of nowadays technology, robot are now being implemented in this situation in order to replace the old-fashioned inspection methods. In this report, the aim of this project is to develop a functional electric cable inspection robot that are able to navigate along electric cables. This robotic device will be able to avoid the electric poles and obstacles as well as to capture and record the defects of the electric cable by using the camera attached to it. This robot need to be in stable condition in order for it not to toppled down or tilt down when doing the inspection. In this project, a new design of the robot are being developed in order for it to achieve its objectives. The user operating system consists of four DC servo motors, two micro DC motor, a remote controller, two cameras, two balancing bar and a screen to display the video feed. This report includes brief discussion on previous methods and robots, theory of operation, design summary, stability analysis and the expected budget for this electric cable inspection robot.